Human mobility in the context of climate change in Sub-Saharan Africa: trends and basic recommendations for development cooperation - Benjamin Schraven; Stephen Adaawen; Christina Rademacher-Schulz; Nadine Segadl (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
This paper provides an overview of what is actually known about the relationship between climate change and human mobility in West, East and Southern Africa – the most affected regions of Sub-Saharan Africa. Although there is a general lack of data on “climate migration”, trends can be deduced from the growing number of case studies and research projects. This paper also formulates some recommendations for German and European development policies for addressing “climate migration” in Africa. The adverse effects of climate change in the three regions are mainly linked to increasing rainfall variability and a higher frequency or intensity of floods and droughts. These effects are a major challenge for human security. The consequences for human mobility, which range from forced displacement to circular labour migration, are embedded in a complex and very context-specific set of political, social, economic, cultural and ecological factors. Due to generally fragile contexts and armed conflicts, the risk of forced displacement in the context of climate change is probably the highest in the Horn of Africa. In all three regions, many households affected by climate change can be considered “trapped” – mobility is not an option for them at all. If mobility is possible, it often takes the form of individual and circular labour migration. Under favourable circumstance (e.g. in the absence of labour exploitation), money earned by migrants might help their households to compensate or at least mitigate the losses induced by climate change (“migration as adaptation”). The ideal political response towards human mobility in the context of climate change is to avoid forced displacement, to maximise positive mechanisms of migration and to minimise negative aspects like labour exploitation. This demands a multi-sectoral and multi-level policy approach. To achieve this, we have formulated the following recommendations: Capacity building and bridging gaps between different policy fields. Dialogue processes between the different (policy) fields and communities need to be fostered. As concepts of migration differ significantly between relevant policy fields, a common understanding of the challenges related to human (im-)mobility in the context of climate change has to be created. Multi-level governance and local empowerment. Open policy spaces should be established and more resources mobilised to strengthen vulnerable groups and communities, which have so far only played a marginal role in relevant policy processes. Collection of data and best practices. The creation of an appropriate database and documentation of best practices regarding the complex problems of local vulnerability and the role of human mobility is absolutely essential for further action. There are severe gaps in this regard.
Keywords: 330; Flucht und Migration; Klimawandel